Charge-induced equilibrium dynamics and structure at the Ag(001)–electrolyte interface. Issue 26 (14th July 2015) - Karl Jr., Robert M.; Barbour, Andi; Komanicky, Vladimir; Zhu, Chenhui; Sandy, Alec; Pierce, Michael S.; You, Hoydoo
<x xml:space="preserve">Abstract</x> The applied potential dependent rate of atomic step motion of the Ag(001) surface in weak NaF electrolyte has been measured using a new extension of the technique of X-ray Photon Correlation Spectroscopy (XPCS).